2008
DOI: 10.2303/jecho.6.1
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Mitral Valve Morphology to Severe Mitral Regurgitation Complicated With Mitral Valve Prolapse

Abstract: Background. Severe mitral regurgitation (MR) is one of the most important complications of mitral valve prolapse (MVP) and it often requires surgical treatment. This study is aimed to assess the relation of mitral valve morphology to severe MR complicated with MVP. Methods.Transesophageal echocardiography was performed in 37 patients with MVP and 30 control subjects.Results. The anterior mitral leaflet (AML) and posterior mitral leaflet (PML) were thicker and longer, and the mitral annulus was larger in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Our study found mild valve leaflet thickening and extensive subvalvular chordae in more than half of RMCT patients, representing almost all pathological types (Figure 1 ). Echocardiography identified that mild valve leaflet thickening accounted for 58.7%, and extensive subvalvular chordae for 53.8% of cases, which may explain why leaflet thickness and length were closely related to the occurrence of RMCT or severe MR [ 17 ]. Echo enhancement and abnormal echo were also very common in all pathological types.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found mild valve leaflet thickening and extensive subvalvular chordae in more than half of RMCT patients, representing almost all pathological types (Figure 1 ). Echocardiography identified that mild valve leaflet thickening accounted for 58.7%, and extensive subvalvular chordae for 53.8% of cases, which may explain why leaflet thickness and length were closely related to the occurrence of RMCT or severe MR [ 17 ]. Echo enhancement and abnormal echo were also very common in all pathological types.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of outward displacements of medial and lateral PMs were different between inferior and anterior MI. This study demonstrated utility of echocardiography to evaluate mitral valve pathophysiology [31]. However, antero-posterior, medio-lateral, and baso-apical components of PM displacements were not investigated.…”
Section: Limitationsmentioning
confidence: 88%